2011
DOI: 10.1093/nar/gkr355
|View full text |Cite
|
Sign up to set email alerts
|

ConTra v2: a tool to identify transcription factor binding sites across species, update 2011

Abstract: Transcription factors are important gene regulators with distinctive roles in development, cell signaling and cell cycling, and they have been associated with many diseases. The ConTra v2 web server allows easy visualization and exploration of predicted transcription factor binding sites in any genomic region surrounding coding or non-coding genes. In this new version, users can choose from nine reference organisms ranging from human to yeast. ConTra v2 can analyze promoter regions, 5′-UTRs, 3′-UTRs and intron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 21 publications
0
45
0
1
Order By: Relevance
“…Putative transcription factor-binding sites in the VEGFA promoter and intron 1 region were identified using the web-based analysis tool ConTra (Broos et al, 46 ). In a Multiz alignment of the promoter (2000 upstream) and first intronic region of VEGFA from different species, highly conserved binding sites were detected for p53, HIF1-a.…”
Section: Methodsmentioning
confidence: 99%
“…Putative transcription factor-binding sites in the VEGFA promoter and intron 1 region were identified using the web-based analysis tool ConTra (Broos et al, 46 ). In a Multiz alignment of the promoter (2000 upstream) and first intronic region of VEGFA from different species, highly conserved binding sites were detected for p53, HIF1-a.…”
Section: Methodsmentioning
confidence: 99%
“…4B, middle and right), the mRNA expression of IGF2 in ESCC cell lines, indicating that E2F1 regulates IGF2 expression at both protein and mRNA levels. Next, two software programs that predict transcription factor-binding sites, namely ConTra V2 and TRRD (25,26), were used to search for potential E2F1-binding sites (BS) in the IGF2 promoter region, and three potential binding sites (designated BS1, BS2, and BS3) were identified by both software, which suggested that E2F1 may bind directly to the IGF2 promoter and activate IGF2 transcription (Fig. 4C).…”
Section: E2f1 Mediates Id1-induced Upregulation Of Igf2 By Binding DImentioning
confidence: 99%
“…Subsequently the ConTra v2 software (Broos et al 2011) was applied to identify potential heat shock factor (HSF) binding sites. Default software parameters were used for the analyses.…”
Section: Analysis Of Cis-regulatory Sequences Of Crmp1mentioning
confidence: 99%